Association Between Obstructive Sleep Apnea Symptoms and Quality of Life in Chronic Obstructive Pulmonary Disease Patients - Muhammad Khoir Gultom; Andika Pradana; Amira Permatasari Tarigan (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is one of the leading causes of mortality worldwide, frequently associated with sleep disturbances, including obstructive sleep apnea (OSA), which may negatively affect patients’ quality of life. This study aimed to describe the demographic characteristics of COPD patients, assess the severity of OSA symptoms and health-related quality of life, and analyze the association between OSA symptoms and quality of life in COPD patients. This quantitative study used a cross-sectional correlational design and was conducted in the Pulmonology Department of Prof.Chairuddin Panusunan Lubis Hospital. A total of 96 COPD patients were recruited using convenience sampling, with inclusion and exclusion criteria. Data were analyzed using univariate and bivariate analyses with the chi-square test at a significance level of α = 0.05. The results demonstrated a significant association between OSA symptoms and health-related quality of life in COPD patients (p = 0.012). Patients with moderate-to-high OSA risk were 2.97 times more likely to experience impaired quality of life compared with those at low risk (OR = 2.97; 95% CI: 1.09–8.09). These findings suggest that OSA symptoms may contribute to reduced quality of life in COPD patients and highlight the importance of early screening and comprehensive management of sleep-related disorders in clinical practice.